The Effectiveness of Padlet Media in Improving the Competence of Writing Biography Texts for Students in Class X-2 at SMA Muhammadiyah 4 Surabaya - Miftahul Afifur Rohman; Mulyono; Resdianto Permata Raharjo (International Journal of Community Engagement Payungi, 2025)
The use of appropriate media is a crucial factor in enhancing students' writing skills, particularly in composing biographical texts. Effective media not only facilitate student engagement but also support the construction of coherent and compelling life narratives. This study aims to examine students' attention levels and evaluate the effectiveness of Padlet as a digital learning medium in improving students’ competence in writing biographical manuscripts. A pre-experimental design with a one-shot case study approach was employed, involving 24 students from Class X-2 selected through cluster sampling. Data were collected using observations and questionnaires, and analyzed through both descriptive and inferential statistical methods. The findings reveal two key outcomes: (1) student attention during the learning process was notably high, with observed activity increasing from 87.92% to 99.33%, supported by a normality test significance value of 0.083; (2) the use of Padlet proved significantly effective, as evidenced by a calculated t-value of 47.54, which far exceeded the critical t-table value of 2.068. These results suggest that Padlet is a valid and effective medium for supporting the teaching and learning of biographical writing. This study contributes to the growing body of research on digital media integration in language learning by empirically demonstrating that Padlet enhances student engagement and writing competence. It provides practical insights for educators seeking innovative tools to improve writing instruction, especially in the context of biographical texts. Moreover, the study reinforces the pedagogical value of interactive platforms in fostering active learning and higher-order thinking skills in secondary education